Evaluation of coffee progenies from crosses between the Icatu and Catimor cultivars (Coffea arabica L.) - Botelho, César Elias; Mendes, Antonio Nazareno Guimarães; Carvalho, Samuel Pereira de; Carvalho, Gladyston Rodrigues de; Gonçalves, Flávia Maria Avelar; Carvalho, Alex Mendonça de (Coffee Science - ISSN 1984-3909, 1970)
The objective of this work was to evaluate the productivity and resistance to leaf rust (Hemileia vastatrix Berk. & Br.) of twenty four F4 coffee progenies from crosses between the Icatu and Catimor cultivars. The experiment was carried out in Três Pontas, Minas Gerais State, in a randomized block design with four repetitions and 25 treatments. The Rubi MG 1192 cultivar was used as control. Coffee bean yield in bags.ha-1 from six harvests (from 2001/2002 to 2006/2007) and leaf rust incidence and severity in the first semester of 2006 were analyzed. The results indicated variability among the evaluated progenies, mainly for grain yield and rust resistance, as confirmed by herdibility traits, which showed a broad range of 31,5% for grain yield and up to 92,8% for rust incidence. This condition, associated with high bean yield, which reached 31,9 bags.ha-1, and with low rust incidence and severity demonstrated the possibility of selecting outstanding progenies from among the studied population, which potentially can be used as productive and commercial cultivars resistant to leaf rust.